Answer:
(x,y,z) = (5/2, 5/2, 0)
If z = t,
(x,y,z) = ((5-3t)/2, (5-t)/2, t)
Step-by-step explanation:
-x + y - z = 0
2y + z = 5
(1/5)z = 0
From eqn 3, z = 0
2y + z = 5
Substitute for z in eqn 2
2y + 0 = 5
y = 5/2
substituting for y and z in eq 1
-x + (5/2) - 0 = 0
x = (5/2)
(x,y,z) = (5/2, 5/2, 0)
In terms of t, if z = t,
eqn 2 becomes 2y + t = 5
2y = 5 - t
y = (5 - t)/2
Eqn1 becomes
-x + (5-t)/2 - t = 0
-x + (5/2) - (t/2) - t = 0
-x + (5/2) - (3t/2) = 0
x = (5-3t)/2
(x,y,z) = ((5-3t)/2, (5-t)/2, t)